Mitigasi Risiko Strategis: Peran Analisis Kelayakan dalam Menjalin keberlanjutan Usaha - Muhammad Fahmi Sholihudin; Sutantri (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
This study aims to analyze the crucial role of feasibility analysis as a strategic risk mitigation instrument in maintaining business continuity amid escalating global uncertainty. The research method employed is library research by synthesizing five selected scholarly articles published between 2020 and 2025. Literature selection was based on methodological diversity, ranging from technical tools such as House of Risk (HoR) to qualitative phenomenological approaches. The findings indicate that risk management has transformed from a mere compliance function into the heart of organizational sustainability strategy. The integration of technical precision (quantitative approach) and the subjective reality of business actors (qualitative approach) is proven to create a more holistic risk identification framework to avoid Black Swan Events. Resulting mitigation strategies include SOP reinforcement, product diversification, hedging strategies, and supply chain collaboration supported by information technology. Feasibility analysis serves as a preventive measure that strengthens the long-term resilience and competitiveness of companies in international markets.